ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMP PADA MATERI LINGKARAN DAN BANGUN RUANG SISI DATAR - Dara Puspita Dewi; Dinar Mediyani; Wahyu Hidayat; Euis Eti Rohaeti; Tommy Tanu Wijaya (IKIP Siliwangi, 2019)
The skill to think critically and mathematics is the basic essential mathematic skills and need to owned by students who study math. This research method use qualitative descriptive research which aims to analyze the student’s mistakes when they do mathematic critical thinking questions on the discussion of circle and flat side geometry. This research subject is 8th grade student who study at one of public junior high school in the city of Purwakarta, Indonesia. The test instrument was 5 essay questions. The research result show that more students have their own difficulties when they do question number 2,3 and 5. I suggested the learning strategy which can upgrade their mathematics critical thinking skill should be used as the learning process.